(untitled) (Revista LIDER, 2019)
The current urban problems require a more strict compliance with the urban standards; however, as the city grows faster than the authority itself can control, it requires instruments or legal figures such as the occupancy certificate that allow you to verify and, if necessary, authorize the reception of the building or development works only when suitable for human security. However, urban norm in the State of Jalisco, México, mixes habitability from the perspective of housing and other times from the perspective of the urban environment: infrastructure and equipment, leaving a void as to ensure that, when facing construction, the surrounding areas to contribute to the development of human beings in social, recreational, security and public services, among other.